A measurement setup for direct 17O MRI at 7 T - Hoffmann, Stefan Heinrich; Begovatz, Paul; Nagel, Armin Michael; Umathum, Reiner; Schommer, Kai; Bachert, Peter; Bock, Michael (Magnetic resonance in medicine, 2011)
An efficient breathing system was designed for direct 17O MRI to perform oxygen metabolism studies of the human brain. The breathing system consists of a demand oxygen delivery device for 17O2 supply and a custom-built re-breathing circuit with pneumatic switching valve. To efficiently deliver the 17O gas to the alveoli of the lungs, the system applies short gas pulses upon an inspiration trigger via a nasal cannula. During and after 17O2 administration, the exhaled gas volumes are stored and filtered in the re-breathing section to make the most efficient use of the rare 17O gas. In an inhalation experiment, 2.2 ± 0.1 L of 70%-enriched 17O2 were administered to a healthy volunteer and direct 17O MRI was performed for a total imaging time of 38 min with a temporal resolution of 50 s per 3D data set. Mapping of the maximum signal increase was carried out showing regional variations of oxygen concentration of up to 30% over the natural abundance of 17O water. Magn Reson Med, 2011. © 2011 Wiley-Liss, Inc.
First published: 09 March 2011
Die 17 im Titel ist hochgestellt
Gesehen am 11.07.2022